A comparative analysis of deep learning and hybrid models to diagnose multi-class skin cancer - Nawrin, Ishrat Nur; Trina, Tonusree Talukder (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2023.